2014
DOI: 10.1021/jp504065e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Osmolyte–Macromolecule Interactions Confer Entropic Stability to Folded States

Abstract: Protective osmolytes are chemical compounds that shift the protein folding/unfolding equilibrium toward the folded state under osmotic stresses. The most widely considered protection mechanism assumes that osmolytes are depleted from the protein's first solvation shell, leading to entropic stabilization of the folded state. However, recent theoretical and experimental studies suggest that protective osmolytes may directly interact with the macromolecule. As an exemplary and experimentally well-characterized sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 62 publications
7
125
1
1
Order By: Relevance
“…The electrostatic interactions between the solute and solution species play only a minor role. 13,72,73 These observations are further supported by another MD simulation study of the effect of trehalose on the protein−urea system, which revealed that Lennard-Jones interactions rather than electrostatic interactions between urea and protein are responsible for urea induced protein denaturation. 35 Contrary to these, Das and Mukhopadhyay 10 argued that the favorable electrostatic interactions between urea and protein cause protein denaturation.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The electrostatic interactions between the solute and solution species play only a minor role. 13,72,73 These observations are further supported by another MD simulation study of the effect of trehalose on the protein−urea system, which revealed that Lennard-Jones interactions rather than electrostatic interactions between urea and protein are responsible for urea induced protein denaturation. 35 Contrary to these, Das and Mukhopadhyay 10 argued that the favorable electrostatic interactions between urea and protein cause protein denaturation.…”
Section: Resultsmentioning
confidence: 57%
“…In this context, it is worth noting that by means of MD simulation studies several attempts have been made in order to understand whether it is the direct electrostatic or van der Waals interactions between urea and protein or a combination of both that is responsible for urea-conferred protein denaturation. 10,13,35,72,73 By estimating dispersion and electrostatic interactions between each water/urea molecule (present in the first solvation shell of the solute and bulk) with solute protein/macromolecule separately, it has been proposed that the favorable van der Waals interactions help to accumulate urea molecules in the first solvation shell of the solute. The electrostatic interactions between the solute and solution species play only a minor role.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of proteins, however, this effect (and related depletion of TMAO) may be muted, as protein surfaces do not necessarily present extended hydrophobic patches (20). In addition to the effect of TMAO crowding, a minor source of stabilization of the protein may arise from an entropic gain resulting from the release of TMAO/water from the vicinity of the protein, as suggested by van der Vegt and coworker (21) in the context of polymer compaction in the presence of urea.…”
Section: Resultsmentioning
confidence: 99%
“…Наприклад, у роботах [3,4] показано, що радiуси макромолекул у розчинi з ростом температури збiльшуються; у роботах [5,6] спостерiгається зменшення радiусiв макромолекул у розчинi з ростом температури. Навiть у межах однiєї рiдинної системи вiдсутня згода у питаннi температурної залежностi радiусiв макромолекул: у роботi [7] показано нелiнiйне зменшення гiдроди-намiчних радiусiв декстрану у водних розчинах з ростом температури, у той самий час у роботi [8] цi залежностi -лiнiйнi.…”
Section: вступunclassified